«RESOURCE» AND «COST-BASED» WAYS OF MEASURING ECONOMIC EFFICIENCY OF PRODUCTION AND THE PROBLEM OF ITS SINGLE EVALUATION - Булаенко, Л. И. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2012)
The article deals with the theoretical research of the advanced resources and expenses which make evaluation of economic efficiency of production based on one generalizing index with “resource” and “cost-based” ways of its measuring impossible. Thus, it is proposed to evaluate the economic efficiency of the production at the industrial enterprises by a number of generalizing data.